Peningkatan Pelayanan KRL dengan Penambahan Gerbong Red Line (Bogor-Jakarta Kota): Analisis Respon dan Persepsi Pengguna di Stasiun Manggarai - Marsya Zusrieka; Chifra Zeila Pramesyanti; Andzi Salwa Salsabila; Hafiz Zaki Hanifan; Ridwan; Faris Widiyatmoko (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study aims to analyze the implementation of the policy of adding train cars to the KRL Red Line (Bogor–Jakarta Kota) and to examine users’ responses and perceptions regarding service improvements at Manggarai Station. The research employed a qualitative approach using a descriptive method. Data were collected through interviews with KRL passengers and station personnel, supported by relevant literature. The findings indicate that the addition of train cars positively improved travel comfort by reducing passenger overcrowding and enhancing mobility. The policy was also perceived as a responsive initiative by the service provider to address increasing passenger demand. However, several challenges remain, including congestion during peak hours, schedule punctuality, and limited operational information. Therefore, continuous improvement efforts are required to enhance service effectiveness, optimize operational performance, strengthen passenger satisfaction, and ensure sustainable, reliable, efficient, and user-oriented public transportation services in the future.